EQ-5D-5L and SF-6Dv2 utility scores in people living with chronic low back pain: a survey from Quebec - Thomas G Poder; Liang Wang; Nathalie Carrier (BMJ Open)
Objective To describe how chronic low back pain (CLBP) impacts on utility scores and which patients’ characteristics most affect these scores in the province of Quebec.Settings Province of Quebec, Canada.Participants 569 adult patients with CLBP.Methods and outcomes An online survey on low back pain was conducted between October 2018 and January 2019. The EuroQol Five Dimensions (EQ-5D-5L) and the Short Form Six Dimensions version 2 (SF-6Dv2) are two generic preference-based measures used to evaluate health-related quality of life (HRQoL) and provide quality-adjusted life-year utility values.Results The number of subjects who agreed to participate was 610, but 41 were excluded because 8 had low back pain for less than 3 months and 33 did not start the survey. A total of 569 subjects were analysed, but only 410 completed the survey up to the EQ-5D-5L or SF-6Dv2 sections. Median (range) of EQ-5D-5L was 0.622 (−0.072 to 0.905), and mean (range) of SF-6Dv2 and EQ-Visual Analogue Scale was 0.561 (0.301–0.829) and 51.0 (0–100), respectively. In all multivariate models, health or life satisfaction increased the health utility score, while pain reduced it. Co-occurring health problems were present for a majority (68%) of participants, mainly fatigue/insomnia (57.4%), musculoskeletal disorder (56.2%) and mental disorder (44%).Conclusion This study provided utility scores with EQ-5D-5L and SF-6Dv2 in patients with CLBP in Quebec, and results were similar to other studies conducted in different settings. These values were well below those reported in the Quebec general population and highlight the association between CLBP and HRQoL.